The Role of Fremantle Indonesia in the X Factor Indonesia Program during the COVID Era - Novia Situmeang (Tradition and Modernity of Humanity, 2026)
This study examines the role of Fremantle Indonesia as a television production company in running the X Factor Indonesia program during the COVID-19 pandemic era (2019–2022). Using a qualitative method through personal experience as a Season 3 contestant and interviews with one of Fremantle's music coordinators, this study describes the changes in Fremantle's production system during the pandemic. The results show that Fremantle successfully adapted its production system by shifting auditions from offline to online, implementing strict health protocols, and utilizing digital platforms to maximize revenue. Despite several challenges such as discrepancies in contestants' vocal quality between online audition videos and live performances, as well as contestant disqualifications due to illness, Fremantle's streaming views actually reached their highest point during 2020–2022. This study concludes that the COVID-19 pandemic, while presenting obstacles, also drove creative innovation that continues to be applied in Fremantle's productions to this day.